Ultrasound-guided aspiration biopsy of subclinical regional metastases of head and neck carcinoma - Višnar-Perovič, Alenka (Radiology and oncology (Ljubljana), 2000)
Background. Studies concerned with the estimation of ultrasound (US) combined with ultrasound-guided aspiration biopsy (USGAB) in the detection of subclinical regional metastases from the planocellular carcinoma of head and neck are promising, but in few cases. Recently, the authors have pointed out the role of lymph node size parameters in order to decide about the use of USGAB. The aim of this study was to test the reliability of US-USGAB for the detection of subclinical regional metastases in patients with planocellular head and neck carcinomas, including the evaluation of lymph node size parameters. Patients and methods. 121 neck sides with no palpable metastases were examined by US in 77 patients with planocellular carcinomas of head and neck. Depending on the results obtained, USGAB was performed on 64 neck sides.After surgery, the results of US-USGAB were compared with histological findings of the dissected lymph nodes. Results. The study showed 77% overall sensitivity of US and USGAB, and 100% specificity, while the versal / longiyudinal diameter was the best predictor of metastatic lymph node involvement. Conclusion. The results of this study established that USGAB is an appropriate method for detection the subclinical regional metastases on neck, and should be included into routine diagnostic work up in the evaluationof the extent of head and necks carcinomas.
Keywords: Bayes theorem; Biopsy, needle; Diagnosis; Diagnostic tests, routine; diagnostika; glava; Head and neck neoplasms; Lymphatic metastasis; Neoplasm metastasis; Pathology; Predictive value of tests; rak (medicina); Sensitivity and specificity; Ultrasonography; ultrazvočna diagnostika; vrat